2014
DOI: 10.1007/s10490-014-9380-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of sexual harassment in Pakistani organizations

Abstract: Despite prior research on the influence of national regulatory and cultural factors on sexual harassment (SH) at the workplace, few studies have examined SH, its impact on victims and redress processes in Muslim majority countries (MMCs) such as Pakistan. This study uses neo-institutional theory to develop a more comprehensive framework to explore SH experienced by women at the workplace in Pakistan. Qualitative methodology is adopted to examine employees' and managers' perceptions of SH. Drawing on interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…This may be attributed not only to the style of work, which is arguably geared toward Western social and capitalist norms, but also to home, where traditional expectations of women as homemakers remain as common practice (Ali and Kramar 2015;Bradley et al, 2005).…”
Section: Wlb and Intersectionalitymentioning
confidence: 99%
“…This may be attributed not only to the style of work, which is arguably geared toward Western social and capitalist norms, but also to home, where traditional expectations of women as homemakers remain as common practice (Ali and Kramar 2015;Bradley et al, 2005).…”
Section: Wlb and Intersectionalitymentioning
confidence: 99%
“…Employer‐provided sexual harassment (SH) training is ubiquitous in the American workplace (Perry, Kulik, Bustamante, & Golom, ) and is becoming increasing common in many other countries as a result of international regulatory developments (e.g., Ali & Kramer, ). It is estimated that U.S. employers alone spend over 10 billion dollars annually on SH training (Goldberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, women who hold low organizational influence, are allegedly more frequent targets of discrimination [98] [99] and harassment at work places [79] [97] [100].…”
Section: Sexual Harassment and Glass Ceiling In Pakistanmentioning
confidence: 99%
“…reported accounts includes staring, sexual comments, molestation and forms of unwanted physical contact, [33] [36] [42] [101]. It is also observed that (87%) Pakistani female university students are reported to be harassed frequently at the cafeterias, classrooms and even in Professor's offices [98] [102], it is also reported female teachers are also frequently harassed in academic institutes [8] [103].…”
Section: Sexual Harassment and Glass Ceiling In Pakistanmentioning
confidence: 99%